Estimating lumbar spine loading during volleyball specific movements using 3d modeling - Funken, J.; Heinrich, B.; Heinrich, K.; Felker, K.; Fett, D.; Platen, P.; Brüggemann, G. P. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Volleyball has a high prevalence of back pain resulting from degenerated intervertebral discs in the lumbar spine. Therefore knowledge about volleyball specific spine loading and its direction is very important. In this study a method is introduced to calculate spine forces in volleyball specific situations also accounting for muscle forces. Two players performed volleyball specific movements in a laboratory environment. Kinematic data were captured by an infrared camera system. An inverse dynamic model was used to calculate spine forces in all three movement planes. Results indicate that the spike has the highest loading. However, peak loading was recognized in phases of takeoff and landing. The presented method was found to be adequate and might be used for further research to get a more comprehensive insight into the topic.